Examining audience perceptions of sexist item songs: A contemporary analysis of bollywood - Forhana Choudhury; Swati Sharma (MethodsX)
Bollywood, better known as the Hindi cinema industry, is globally renowned for its entertainment, yet it grapples with a persistent issue - the prevalence of sexist item songs. These dance sequences often objectify female actors, but prevalent research has predominantly focused on their consequences rather than the reasons behind their continued creation and acceptance.The paper traces the historical evolution of item songs and their socio-cultural root causes responsible for production and distribution. A mixed method approach was employed, data were collected from 310 working professionals using a convenience sampling technique and a thorough review of 62 articles from databases like Jstor, ProQuest, Google Scholar, and Springer. By employing a mixed method approach, this research statistically analyses the critical socio-cultural factors contributing to sexist song production, the societal impact of such songs, and the root causes of their depiction. • The approach explores how Bollywood reinforces gender norms through rewards and punishments, perpetuating the conformity of women to stereotypical roles. • Additionally, it investigates the Male Gaze theory in the context of Bollywood's portrayal of women as objects of desire. • It applies Cognitive Dissonance to understand the audience's resistance to change despite awareness of the harm caused by sexist songs.